1976
DOI: 10.1002/chin.197644149
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: BROMINATION OF FUNCTIONAL DERIVATIVES OF SOME VINYLACETYLENE HYDROCARBONS AND SILICON HYDROCARBONS

Abstract: Die carboxylierten Vinylacetylene (I) und (II) werden in Tetrachlorkoh1enstoff an der Doppel‐ und an der Dreifachbindung zu (III) und (V) bzw. (IV) und (VI) bromiert.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0
1

Year Published

1977
1977
2007
2007

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
4
0
1
Order By: Relevance
“…The imidazolium salts were deprotonated in situ by the base sodium tert ‐butoxide to afford the corresponding carbene. The results of a screening of the ligand and the copper salt, using propargyl oxirane 3 a 14 and polymethylhydridosiloxane (PMHS) as the stoichiometric hydride source, are summarized in Table 1…”
Section: Methodsmentioning
confidence: 99%
“…The imidazolium salts were deprotonated in situ by the base sodium tert ‐butoxide to afford the corresponding carbene. The results of a screening of the ligand and the copper salt, using propargyl oxirane 3 a 14 and polymethylhydridosiloxane (PMHS) as the stoichiometric hydride source, are summarized in Table 1…”
Section: Methodsmentioning
confidence: 99%
“…( E )-6-(Trimethylsilyl)-3-hexen-5-yn-2-one (7b). Obtained as a light-yellow oil ( trans:cis = 97:3) after flash chromatography (5% ether in pentane, R f = 0.23), 78% yield. 1 H NMR: δ 6.59 (d, J = 16, 1H), 6.51 (d, J = 16, 1H), 2.26 (s, 3H), 0.22 (s, 9H).…”
Section: Methodsmentioning
confidence: 99%
“…Sir: Recently we described the conjugate addition of B-lalkynyl-9-borabicyclo[3.3.1]nonanes to a variety of ,ß-unsaturated ketones, which provided a valuable synthesis of , -alkynyl ketones.2 House has suggested that reduction potentials may be used to determine the suitability of substrates toward conjugate addition of organocuprates and perhaps other organometallic reagents. 3 Hooz and Layton, in their work on dialkylalkenyl alanés and dialkylalkynyl alanés, point out that the yields of conjugate addition product appear to correlate well with the reduction potentials of the substrates utilized.4 Reaction time % GC yield (£)-4-Methoxy-3-buten-2-one (5) (£)-7,7-Dimethyl-3-octen-5-yn-2-one lh 100 (£)-4,4-Dimethyl-l-methoxy-l-penten-3-one (6) (£)-2,2,8,8-Tetramethyl-4-nonen-6-yn-3-one lh 100 (£)-3-Methoxy-l-phenyl-2-propen-l-one (7) (£)-6,6-Dimethyl-l-phenyl-2-hepten-4-yn-l-one lh 65 (£)-l-Methoxy-2-methyl-l-penten-3-one (8) (£)-4,8,8-Trimethyl-4-nonen-6-yn-3-one c Measured by NMR. d It is interesting to note that the reaction of this methoxy enone with B-l-hexynyl-9-BBN provided a 70% isolated yield of 3-decen-5-yn-2-one after 5 days.…”
mentioning
confidence: 92%